X-rays - Morrison, Rob; Black, Don (Nelson Australia Melbourne, Vic., 1994)
The book X-Rays by Rob Morrison explores the science, history, and applications of X-rays. It covers the discovery of X-rays by Wilhelm Röntgen, their impact on medical diagnostics, and their broader use in fields like industry, security, and astronomy. Morrison explains the principles behind X-ray imaging, its benefits in non-invasive medical procedures, and safety concerns related to radiation exposure. The book is likely written in an accessible style, aimed at readers who are interested in understanding the technology and its far-reaching implications in modern life.